Kompetensi Sosial Guru Pendididkan Agama Islam dalam Mengatasi Kesulitan Belajar Peserta Didik Kelas VII MTs Misbahul Falah Ciseureuh - usep rusmana (Pergunu Jawa Barat, 2021)
This research is motivated by the learning difficulties of students at MTs Misbahul Falah Ciseureuh, some students are still slow in learning religion, especially on local content material juz 'amma. The lack of PAI teachers in applying social competence is one of the causes of learning difficulties experienced by students. The purpose of this study was to identify and analyze the process of applying PAI teacher social competence, types of learning difficulties experienced by students, supporting and inhibiting factors in the process of applying PAI teacher social competence in overcoming students' learning difficulties and the results of the PAI teacher social competence process in overcoming learning difficulties. learners. This study uses a phenomenological approach and qualitative methods. The results showed that the process of applying the social competence of PAI teachers and their indicators of inclusive, non-discriminatory, adaptive and communicative PAI teachers at MTs Misbahul Falah was less than optimal.